Tuning the properties of pH responsive nanoparticles to control cellular interactions in vitro and ex vivo. Issue 38 (19th September 2016) - Mann, S. K.; Dufour, A.; Glass, J. J.; De Rose, R.; Kent, S. J.; Such, G. K.; Johnston, A. P. R.
Abstract : Engineering the properties of nanoparticles to limit non-specific cellular interactions is critical for developing effective drug delivery systems. Differences between interactions with cultured cells and human blood highlights the need for appropriate assays. Abstract : Engineering the properties of nanoparticles (NPs) to limit non-specific cellular interactions is critical for developing effective drug delivery systems. In this study we investigate the differences in non-specific cell association between polymer NPs prepared with linear polyethylene glycol (PEG) and brush PEG both in vitro and ex vivo . Most studies to investigate the non-fouling properties of NPs have been performed using cell-line based assays. However, in this study we demonstrate a whole blood assay using fresh human blood. It is likely this assay reflects more accurately the fate of NPs when injected into human blood in vivo . Non-linear PEG analogues such as poly(poly(ethylene glycol)methacrylate) (PEGMA) are attractive alternatives to linear PEG as hydrophilic coatings for NP drug delivery systems due to their simple and versatile synthesis. We prepared NPs composed of a poly(2-diethylamino)ethyl methacrylate (PDEAEMA) core and a diblock copolymer of PDEAEMA and either linear PEG or brush PEGMA. These NPs depend on low-fouling properties of the hydrophillic PEG coating to avoid uptake by the mononuclear phagocyte system (MPS). In vitro cell association assays showed brush PEGMA NPs exhibited lower association with 3T3 fibroblast and C1R lymphoblast cells compared to linear PEG NPs. In an ex vivo whole blood assay, brush PEGMA nanoparticles showed similar low association with monocytes and granulocytes as linear PEG NPs with a similar length PEG component. Higher association with blood cells was observed for NPs containing a lower molecular weight PEGMA component, despite having the same molecular weight as the linear PEG NPs (2 kDa). The results demonstrate that trends observed in cell-lines are not always consistent with assays in more complex systems such as blood. Based on these results the reported PEGMA NPs are attractive alternatives to our previously reported linear PEG NPs.